Developing English Speaking Materials Based on The Contextual Teaching and Learning for Grade XI Senior High School in SMA Negeri 1 Kerajaan - Friski Padang; Sumarsih Sumarsih; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2018)
This study aim to design English speaking materials needed for students of class XI SMA N 1 Kerajaan. This study was conducted by using Research and Development (R & D) design through six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product. The subject of this study were students of class XI consisting of 20 students. The instruments for collecting the data were questionnaire and interview. After analyzing the data, the writer got the students’ needs. The data were gathered by administering interview to the English teacher and distributing the questionnaire to 20 respondents to get the students’ needs. The interview and questionnaire result of the needs analysis showed that the students needed materials for speaking which were attractive and interesting and based on their social life context. Thus, the learning materials were developed into 6 of speaking material. By two experts; English lecturer and English teacher. The average scores are 4,7 or 95% from English Lecturer and 4,5 or 90% from English Teacher. It means the developing materials categorized as relevant, thus, it can be concluded that contextual teaching and learning speaking materials had been appropriated for grade XI students of Senior High School.Key words: Research and Development (R & D), Speaking materials, Contextual Teaching and Learning